Peran Mahasiswa Dalam Pemberdayaan Masyarakat Desa Lau Simomo Melalui Program Edukasi, Keagamaan dan Sosial Pada Kegiatan Kuliah Kerja Nyata - Naufal Akbar Batubara; Zulfahmi Lubis; Amira Mufidah Harahap; Dian Mutiara Simamora; Ika Puspita Sari (Pusdikra Publishing, 2025)
The main objective of this study is to explore the role of university students in empowering the community of Lau Simomo Village through educational, religious, and social activities carried out during the Community Service Program (KKN). This research employed a descriptive qualitative approach with a field study method to provide a direct understanding of the conditions in the community. The data were obtained from both primary and secondary sources. Primary data were collected from the residents of Lau Simomo Village, Karo Regency, while secondary data included documentation, personal notes, and related references. Data collection techniques consisted of interviews, observations, and documentation. The findings reveal that the KKN program brought positive outcomes for both the villagers and the students. In the educational field, tutoring in the village library encouraged children’s motivation to learn, enriched teaching variations at schools, and introduced entrepreneurial insights through the socialization of banana chips production. Anti-bullying counseling helped foster respect among children. In terms of religion, activities such as wirid, Friday sermons, and Qur’an recitation lessons strengthened the community’s spiritual values. Socially, collective work, mango tree planting, and visiting non-Muslim residents during bereavement enhanced solidarity and tolerance. Overall, the KKN program provided tangible benefits for society while offering valuable experiences for students in community engagement.